Al-Qosimi sebagai Metode Pembelajaran Tahfiz Alquran: Studi Deskriptif di Rumah Tahfidz Sang Surya Perguruan Mu’allimin - Wira Meiris Tri Agusman (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2021)
The development of Qur'anic tahfidz learning and the methods used so rapidly in Indonesia, and each method used has its own characteristics in implementing it, so that learning outcomes are also different from the differences in learning methods used. The study aims to describe the use of al-Qosimi as a method of teaching the Qur'anic tahfidz. To achieve this goal, researchers use qualitative methods, research data sources are learners and teachers tahfidz, research data analyzed descriptively. The findings of the study proved that al-Qosimi methods have a significant impact in improving the qur'anic memorized learners. The use of alqosimi methods makes it easier for learners to remember and Increase memorization, this is proven by the running of the tahfidz house program for 2 years has been able to graduate 53 learners.